Identifikasi Sumber Air Tanah dalam Berdasarkan Analisis Data Resistivitas di Daerah Bandara Adi Soemarmo, Solo, Jawa Tengah - Caga Setia; Darsono D; Cari C (Department of Physics, Sebelas Maret University, 2016)
The research was around in the Adi Soemarmo Airport area, Solo, Central Java. The growing development and the increased need for water to be basic the importance of this research. The purpose of this research to sources of ground water and state of rocks lithology. This Research using geoelectric method Schlumberger configuration using tools resistivitiy McOHM OYO Model 2119C-EL. The measurements were made much as 6 point sounding, electrode AB/2stretch scattered around the Adi Soemarmo Airport with varying penetration depths ranging from 1.5 meters up to 400 meters with stretch of the electrode reaches 800 meters. Furthermore, the value of resistivity in the field measurements made longitudinal section and water content analysis approached using IP2WIN interpretation software. the results of the study showed that at the point of sounding 2, 1, and 3 at depths greater than 130 meters areallegedly identified the source of ground water and the at point of sounding 7, 4, and 5 over 100 meters.